Construction and Validation of a Five-Dimensional Celebrity Endorsement Scale: Introducing the Pater Model - Gupta, Ruchi; Nawal Kishor, Prof; Verma, DPS (British Journal of Marketing Studies, 2017)
Research has shown that the use of celebrity endorsers brings many positive effects including a positive brand attitude, building brand awareness, creating positive feelings towards the ad and increased purchase intention for the brand. However, the process of choosing the right celebrity for the brand is not easy. It is important for the companies to choose an effective celebrity as their brand ambassador. The purpose of the present study is to construct and validate a scale that the marketing managers can use to select an effective celebrity endorser for their products/brands. Through a survey of 692 respondents in India who are exposed to celebrity endorsements for various products/brands, a five-dimensional scale measuring various attributes of a celebrity endorser is revealed through exploratory factor analysis. The scale is empirically tested for unidimensionality, reliability, convergent validity and discriminant validity, using confirmatory factor analysis. The resultant validated instrument comprises of five dimensions of celebrity endorsers including attractiveness, trustworthiness, expertise, popularity and relevance. Thus, the present study presents a new model – PATER model of celebrity endorsements, defining the important attributes that should be considered in making a choice of the celebrity endorser.